Membangun Citra Pemerintah melalui Media Sosial: Strategi Komunikasi Pemprov Lampung di Era Digital - Nurika, Sierta Putri; Aiyanti, Nina Yudha; Utaridah, Nanda; Kartika, Tina; Putra, Purwanto (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The development of information and communication technology has encouraged local governments to utilize social media as a strategic tool for delivering information, building a positive image, and establishing two-way communication with the public. This study aims to analyze the digital communication strategies implemented by the Provincial Government of Lampung in shaping a responsive and transparent government image in the digital era. This research employs a descriptive qualitative method, with data collection techniques including direct observation of the official social media accounts of the Provincial Government of Lampung, in-depth interviews with three key informants from the social media management team at the Department of Communication, Informatics, and Statistics, as well as documentation of uploaded digital content. The findings show that the Lampung Provincial Government actively produces and distributes informative and educational content, including government agendas, regional policies, and local cultural promotion. The content is presented in engaging visual formats, such as infographics and short videos, tailored to reach younger audiences. During one month of observation, the Instagram account @lampungprovgoid recorded 209,406 impressions, 5,089 interactions, and an increase of 395 new followers. Strategy evaluation is conducted through media analytics tools, public sentiment analysis, and regular issue monitoring. Although the strategy has shown positive results, challenges such as the spread of hoaxes, negative comments, limited human resources, and the influence of social media algorithms remain obstacles. Overall, the digital communication strategy of the Lampung Provincial Government has proven effective in strengthening public trust and building a government image that is open, modern, and adaptive.